Study of the interactions of pions in the CALICE silicon-tungsten calorimeter prototype - Adloff, Catherine; Schultz-Coulon, Hans-Christian; Shen, Wei (Journal of Instrumentation, 2010)
A prototype silicon-tungsten electromagnetic calorimeter for an ILC detector was tested in 2007 at the CERN SPS test beam. Data were collected with electron and hadron beams in the energy range 8 to 80 GeV. The analysis described here focuses on the interactions of pions in the calorimeter. One of the main objectives of the CALICE program is to validate the Monte Carlo tools available for the design of a full-sized detector. The interactions of pions in the Si-W calorimeter are therefore confronted with the predictions of various physical models implemented in the GEANT4 simulation framework.
*The CALICE collaboration: C. Adloff, H.-C. Schultz-Coulon, W. Shen [und 155 weitere Personen]
Gesehen am 16.11.2022